Comparison of ambient aerosol extinction coefficients obtained from in-situ, MAX-DOAS and LIDAR measurements at Cabauw - Zieger, Paul; Weingartner, E.; Henzing, J.; Moerman, M.; de Leeuw, G.; Mikkilä, J.; Ehn, M.; Petäjä, T.; Clémer, K.; van Roozendael, M.; Yilmaz, Selami; Frieß, Udo; et al. (Atmospheric chemistry and physics, 2011)
In the field, aerosol in-situ measurements are often performed under dry conditions (relative humidity RH<30–40%). Since ambient aerosol particles experience hygroscopic growth at enhanced RH, their microphysical and optical properties – especially the aerosol light scattering – are also strongly dependent on RH. The knowledge of this RH effect is of crucial importance for climate forcing calculations or for the comparison of remote sensing with in-situ measurements. Here, we will present results from a four-month campaign which took place in summer 2009 in Cabauw, The Netherlands. The aerosol scattering coefficient σsp(λ) was measured dry and at various, predefined RH conditions between 20 and 95% with a humidified nephelometer. The scattering enhancement factor f(RH,λ) is the key parameter to describe the effect of RH on σsp(λ) and is defined as σsp(RH,λ) measured at a certain RH divided by the dry σsp(dry,λ). The measurement of f(RH,λ) together with the dry absorption measurement (assumed not to change with RH) allows the determination of the actual extinction coefficient σep(RH,λ) at ambient RH. In addition, a wide range of other aerosol properties were measured in parallel. The measurements were used to characterize the effects of RH on the aerosol optical properties. A closure study showed the consistency of the aerosol in-situ measurements. Due to the large variability of air mass origin (and thus aerosol composition) a simple parameterization of f(RH,λ) could not be established. If f(RH,λ) needs to be predicted, the chemical composition and size distribution need to be known. Measurements of four MAX-DOAS (multi-axis differential optical absorption spectroscopy) instruments were used to retrieve vertical profiles of σep(λ). The values of the lowest layer were compared to the in-situ values after conversion of the latter ones to ambient RH. The comparison showed a good correlation of R2 = 0.62–0.78, but the extinction coefficients from MAX-DOAS were a factor of 1.5–3.4 larger than the in-situ values. Best agreement is achieved for a few cases characterized by low aerosol optical depths and low planetary boundary layer heights. Differences were shown to be dependent on the applied MAX-DOAS retrieval algorithm. The comparison of the in-situ extinction data to a Raman LIDAR (light detection and ranging) showed a good correlation and higher values measured by the LIDAR (R2 = 0.82−0.85, slope of 1.69–1.76) if the Raman retrieved profile was used to extrapolate the directly measured extinction coefficient to the ground. The comparison improved if only nighttime measurements were used in the comparison (R2 = 0.96, slope of 1.12).
Gesehen am 19.01.2023